Light material and preparation method thereof, middle frame and electronic equipment

By setting a modified magnesium oxide ceramic layer, an aluminum -based bottom layer and a dense enhancement layer on the magnesium fundamental substrate, the problem of poor corrosion resistance of magnesium fundamentals is solved, and the good corrosion resistance of the chlorine corrosion environment is realized. At the same time, Maintain the lightweight characteristics of the material.

CN119352019APending Publication Date: 2025-01-24REALME MOBILE TELECOMM SHENZHEN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411520556.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Magnesium-based metals have poor corrosion resistance and are easily corroded in corrosion environments containing chloride ions.

Method used

A modified magnesium oxide ceramic layer, an aluminum-based base layer and a dense reinforcement layer are respectively provided on the magnesium-based metal substrate. The modified magnesium oxide ceramic layer is formed by micro-arc oxidation, and the aluminum-based base layer and dense reinforcement layer are formed by physical vapor deposition. The density of the dense reinforcement layer is higher than that of the aluminum-based base layer.

Benefits of technology

It significantly improves the corrosion resistance of the magnesium fundamental material, and can form a passivation film in a corrosive environment containing chloride ions to play a good corrosion -resistant effect, while maintaining the lightweight characteristics of lightweight materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352019A_ABST
    Figure CN119352019A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic equipment, in particular to a light material and a preparation method thereof, a middle frame and electronic equipment. The light material comprises: a magnesium-based metal matrix; the modified magnesium oxide ceramic layer is positioned on the magnesium-based metal matrix; the aluminum-based bottoming layer is located on the modified magnesium oxide ceramic layer, and the density of the aluminum-based bottoming layer is larger than that of the modified magnesium oxide ceramic layer; and the compact reinforcing layer is located on the aluminum-based bottoming layer, and the density of the compact reinforcing layer is larger than that of the aluminum-based bottoming layer. The light material provided by the invention meets the requirement of light weight, and also has better corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic equipment, and in particular to a lightweight material and a preparation method thereof, a middle frame and an electronic equipment. Background Art

[0002] Lightweighting is one of the main development directions of modern industry. With the increasing market demand for lightweight materials, magnesium-based lightweight metals represented by magnesium alloys are increasingly appearing in people's vision. Compared with traditional stainless steel materials, titanium alloy materials and aluminum alloy materials, magnesium-based metals have great advantages in weight, but magnesium-based metals are relatively active, the surface is easily oxidized, and the potential of magnesium-based metals is low, so they are easily corroded. Summary of the invention

[0003] Based on this, the present application provides a lightweight material and a preparation method thereof, a middle frame and an electronic device, the purpose of which is to improve the problem of poor corrosion resistance of magnesium-based metals.

[0004] The first aspect of the present application provides a lightweight material, and its technical solution is as follows:

[0005] A lightweight material comprising:

[0006] Magnesium-based metal matrix;

[0007] A modified magnesium oxide ceramic layer is located on the magnesium-based metal substrate;

[0008] An aluminum-based primer layer is located on the modified magnesium oxide ceramic layer, and the density of the aluminum-based primer layer is greater than that of the modified magnesium oxide ceramic layer;

[0009] The dense reinforcement layer is located on the aluminum-based primer layer, and the density of the dense reinforcement layer is greater than that of the aluminum-based primer layer.

[0010] The second aspect of the present application provides a method for preparing a lightweight material, and its technical solution is as follows:

[0011] A method for preparing a lightweight material comprises the following steps:

[0012] forming a modified magnesium oxide ceramic layer on a magnesium-based metal substrate by micro-arc oxidation;

[0013] Depositing an aluminum-based primer layer on the modified magnesium oxide ceramic layer by physical vapor deposition, wherein the aluminum-based primer layer has a higher density than the modified magnesium oxide ceramic layer;

[0014] A dense reinforcement layer is deposited on the aluminum-based primer layer by physical vapor deposition, and the power supply is controlled to be a pulse power supply, so that the density of the dense reinforcement layer is greater than that of the aluminum-based primer layer.

[0015] The third aspect of the present application provides a middle frame, and its technical solution is as follows:

[0016] A middle frame comprises the lightweight material as described above.

[0017] A fourth aspect of the present application provides an electronic device, and its technical solution is as follows:

[0018] An electronic device, comprising a display module, a middle frame, a circuit board and a housing, wherein the middle frame comprises the lightweight material as described above or the middle frame is as described above;

[0019] The display module, the middle frame and the housing are arranged to form a receiving space;

[0020] The circuit board is located in the accommodating space and is electrically connected to the display module.

[0021] This application has the following beneficial effects:

[0022] The present application sets a modified magnesium oxide ceramic layer, an aluminum-based primer layer and a dense reinforcement layer on the magnesium-based metal substrate, wherein the modified magnesium oxide ceramic layer has good corrosion resistance and wear resistance, but the modified magnesium oxide ceramic layer has large pores. Therefore, the present application sets a dense aluminum-based primer layer on the modified magnesium oxide ceramic layer, and the aluminum-based primer layer has good bonding with the modified magnesium oxide ceramic layer, and the potential of Al (-1.663V) is close to the potential of magnesium (-2.363V), and the tendency of electrochemical corrosion is smaller. On this basis, the present application also forms a denser dense reinforcement layer on the aluminum-based primer layer, which can significantly reduce the channels for ions to enter the magnesium-based metal substrate, greatly improve the corrosion resistance of the magnesium-based metal substrate, and can form a good passivation film in a corrosive environment containing chloride ions, which plays a good corrosion resistance role. In summary, the lightweight material of the present application uses a magnesium-based metal substrate, which meets the requirements of lightweight and also has good corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0024] Figure 1 is a schematic structural diagram of a lightweight material according to one embodiment;

[0025] Figure 2 A schematic structural diagram of a lightweight material according to another embodiment;

[0026] Figure 3 is a schematic diagram of the structure of a dense reinforcement layer in an example;

[0027] Figure 4 A schematic structural diagram of a lightweight material according to another embodiment;

[0028] Figure 5 This is a schematic structural diagram of a lightweight material according to yet another embodiment;

[0029] Figure 6 This is a schematic diagram of a preparation process of a lightweight material according to an embodiment;

[0030] Figure 7 A schematic diagram of a preparation process of a lightweight material according to another embodiment;

[0031] Figure 8 A schematic diagram of a preparation process of a lightweight material according to another embodiment;

[0032] Fig. 9 The diagram is a schematic structural diagram of a lightweight material according to yet another embodiment. DETAILED DESCRIPTION

[0033] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0035] the term

[0036] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:

[0037] In this application, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In this application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0038] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0039] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0040] In the present application, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0041] In the present application, when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may also be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time. It should also be understood that when explaining the connection relationship or positional relationship of elements, although not explicitly described, the connection relationship and positional relationship are interpreted as including an error range, which should be within the acceptable deviation range of a specific value determined by a person skilled in the art.

[0042] In this application, the density of the coating is calculated by the SEM image of the coating cross section. According to the SEM image, the surface area of ​​the pores and defects in the SEM image is first measured, and then divided by the surface area shown in the SEM image to obtain the proportion of pores and defects. 1-the proportion of pores and defects is the density of the coating of this application. Among them, the fewer the number of pores and defects, the higher the density of the coating.

[0043] In view of the poor corrosion resistance of magnesium-based metals, the first aspect of the present application provides a lightweight material, see Figure 1 In one embodiment, the lightweight material 100 includes a magnesium-based metal substrate 11, a modified magnesium oxide ceramic layer 12, and an aluminum-based primer layer 13. The modified magnesium oxide ceramic layer 12 is located on the magnesium-based metal substrate 11, the aluminum-based primer layer 13 is located on the modified magnesium oxide ceramic layer 12, and the aluminum-based primer layer 13 has a greater density than the modified magnesium oxide ceramic layer 12.

[0044] The magnesium-based metal matrix 11 can be a magnesium matrix or a magnesium alloy matrix. Taking magnesium alloy metal as an example, the density of stainless steel is about 7.8g / cm³, the density of titanium alloy is about 4.5g / cm³, the density of aluminum alloy is 2.7g / cm³, and the density of magnesium alloy is about 1.8g / cm³. It can be seen that magnesium alloy has great advantages in lightness, thinness and weight reduction.

[0045] The modified magnesium oxide ceramic layer 12 is located on the magnesium-based metal substrate 11, and the modified magnesium oxide ceramic layer 12 is generally formed by micro-arc oxidation. Micro-arc oxidation (abbreviated as MAO) refers to the growth of a modified ceramic coating mainly composed of magnesium oxide and supplemented by electrolyte components on the surface of the magnesium-based metal substrate under the instantaneous high temperature and high pressure generated by arc discharge, relying on the matching and adjustment of electrolyte and electrical parameters. Optionally, the modified magnesium oxide ceramic layer includes Mg(OH)2 and Al2O3. After the modified magnesium oxide ceramic is formed on the magnesium-based metal substrate by micro-arc oxidation, the modified magnesium oxide ceramic layer has good corrosion resistance and wear resistance, and has a positive effect on improving the corrosion resistance of the magnesium-based metal substrate. Optionally, the thickness of the modified magnesium oxide ceramic layer is 10μm~20μm. For example, the thickness of the modified magnesium oxide ceramic layer is 10μm, 12μm, 15μm, 18μm, and 20μm.

[0046] However, the density of the modified magnesium oxide ceramic layer is limited. Generally speaking, the density of the modified magnesium oxide ceramic layer is 80% to 85%. For example, the density of the modified magnesium oxide ceramic layer is 80%, 81%, 82%, 83%, 84%, and 85%. There will be large pores, which will affect the further improvement of the corrosion resistance of the magnesium-based metal substrate. In this embodiment, an aluminum-based primer layer 13 is provided on the modified magnesium oxide ceramic layer 12. The density of the aluminum-based primer layer 13 is greater than that of the modified magnesium oxide ceramic layer 12. The aluminum-based primer layer 13 can be formed by physical vapor deposition. Optionally, the density of the aluminum-based primer layer is 92% to 95%. For example, the density of the aluminum-based primer layer is 92%, 93%, 94%, and 95%. After the aluminum-based primer layer 13 is provided, the aluminum-based primer layer 13 not only has a good bonding force with the modified magnesium oxide ceramic layer 12, but also the potential potential of Al (-1.663V) is close to the potential potential of magnesium (-2.363V), and the tendency of electrochemical corrosion is smaller.

[0047] Optionally, the thickness of the aluminum-based primer layer is 0.2 μm to 0.5 μm. For example, the thickness of the aluminum-based primer layer is 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm. Optionally, the aluminum-based primer layer includes one or more layers of an Al layer, an AlN layer, an AlON layer, or an AlCrN layer. Preferably, the aluminum-based primer layer includes a stacked Al layer and an AlN layer, and the Al atoms in the Al layer can refine the grains of the AlN layer. The coating with finer grains can effectively prevent the expansion of cracks and reduce the channels for ion entry.

[0048] Compared with forming a single corrosion-resistant coating directly on a magnesium-based metal substrate by electroplating and chemical plating, the cost of the lightweight material of the above structure is relatively low. Compared with forming a single corrosion-resistant coating directly on a magnesium-based metal substrate by anodizing and MAO, the corrosion resistance of the lightweight material of the above structure is higher. Compared with forming a single corrosion-resistant coating directly on a magnesium-based metal substrate by physical vapor deposition, the bonding strength of the layers of the above lightweight material is better.

[0049] To further improve the corrosion resistance of magnesium-based metal substrates, see Figure 2 In another embodiment, the lightweight material 200 includes a magnesium-based metal substrate 21, a modified magnesium oxide ceramic layer 22, an aluminum-based primer layer 23, and a dense reinforcement layer 24. The modified magnesium oxide ceramic layer 22 is located on the magnesium-based metal substrate 21, the aluminum-based primer layer 23 is located on the modified magnesium oxide ceramic layer 22, the dense reinforcement layer 24 is located on the aluminum-based primer layer 23, and the density of the aluminum-based primer layer 23 is greater than that of the modified magnesium oxide ceramic layer 22, and the density of the dense reinforcement layer 24 is greater than that of the aluminum-based primer layer 23.

[0050] The above embodiment not only sets an aluminum-based base layer 23 on the modified magnesium oxide ceramic layer 22, but also sets a dense reinforcement layer 24 on the aluminum-based base layer 23 that is denser than the aluminum-based base layer 23. The dense reinforcement layer 24 can be formed by physical vapor deposition, and a dense reinforcement layer 24 that is denser than the aluminum-based base layer 23 can be formed by selecting a power source for physical vapor deposition. Optionally, the density of the dense reinforcement layer 24 is 97% to 99%. For example, the density of the dense reinforcement layer 24 is 97%, 98%, and 99%. The provision of the dense reinforcement layer 24 can significantly reduce the channels for ions to enter the magnesium-based metal matrix, greatly improve the corrosion resistance of the magnesium-based metal substrate, and can form a better passivation film in a corrosive environment containing chloride ions, which plays a good corrosion resistance role. Optionally, the thickness of the dense reinforcement layer is 0.8μm to 1.2μm. For example, the thickness of the dense reinforcement layer is 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, or 1.2 μm.

[0051] In one example, the dense reinforcement layer 24 is a single layer. Optionally, the single layer of dense reinforcement layer 24 is selected from AlN layer, CrN layer, CrAlN layer, TiAlN layer, TiSiAlN layer, TiCN layer, CrCN layer, CrSiN layer or TiSiN layer. Preferably, the dense reinforcement layer 24 includes Al element. In this case, the dense reinforcement layer 24 has better bonding strength with the aluminum-based primer layer 23.

[0052] In another example, the dense reinforcement layer 24 includes a plurality of stacked reinforcement sub-layers. Compared with a single-layer dense reinforcement layer, the dense reinforcement layer with a plurality of stacked reinforcement sub-layers has a higher hardness at the same thickness.

[0053] The multiple reinforcement sublayers can be stacked in disorder or in order. Optionally, in the multiple reinforcement sublayers, the content of at least one element in each reinforcement sublayer increases gradually along the stacking direction. In an example, see Figure 3 The dense reinforcement layer 24 includes a stacked first reinforcement sublayer 241, a second reinforcement sublayer 242, a third reinforcement sublayer 243 and a fourth reinforcement sublayer 244, wherein the first reinforcement sublayer 241, the second reinforcement sublayer 242, the third reinforcement sublayer 243 and the fourth reinforcement sublayer 244 all include element A, the content of element A in the first reinforcement sublayer 241 is Xwt%, the content of element A in the second reinforcement sublayer 242 is (X+Y)wt%, the content of element A in the third reinforcement sublayer 243 is (X+2Y)wt%, and the content of element A in the fourth reinforcement sublayer 244 is (X+3Y)wt%.

[0054] Optionally, the multiple reinforcement sublayers are each independently selected from AlN layer, CrN layer, CrAlN layer, TiAlN layer, TiSiAlN layer, TiCN layer, CrCN layer, CrSiN or TiSiN. Preferably, the multiple reinforcement sublayers all include Al element. In this case, the bonding force between the multiple reinforcement sublayers is good, and the bonding force with the aluminum-based primer layer 23 is also good.

[0055] The above-mentioned embodiment sets a dense aluminum-based primer layer on the modified magnesium oxide ceramic layer. Not only does the aluminum-based primer layer have a good bonding force with the modified magnesium oxide ceramic layer, but the potential of Al (-1.663V) is close to the potential of magnesium (-2.363V), and the tendency of electrochemical corrosion is smaller. On this basis, a denser dense reinforcement layer is also set on the aluminum-based primer layer, which can significantly reduce the passage of ions entering the magnesium-based metal matrix. Through the cooperation of the aluminum-based primer layer and the dense reinforcement layer, the problem of poor corrosion resistance of magnesium-based metals can be significantly improved, and it can play a good corrosion resistance role in a corrosive environment containing chloride ions. The lightweight material of this embodiment has excellent corrosion resistance and has great application potential in 3C electronic products.

[0056] In another embodiment, the lightweight material further includes a decorative layer. In this case, the lightweight material can be given a decorative effect. Figure 4 The lightweight material 300 includes a magnesium-based metal matrix 31, a modified magnesium oxide ceramic layer 32, an aluminum-based base layer 33, a dense reinforcement layer 34 and a decorative layer 35, wherein the modified magnesium oxide ceramic layer 32 is located on the magnesium-based metal matrix 31, the aluminum-based base layer 33 is located on the modified magnesium oxide ceramic layer 32, the dense reinforcement layer 34 is located on the aluminum-based base layer 33, the decorative layer 35 is located on the dense reinforcement layer 34, and the density of the aluminum-based base layer 33 is greater than that of the modified magnesium oxide ceramic layer 32, and the density of the dense reinforcement layer 34 is greater than that of the aluminum-based base layer 33.

[0057] The composition and color of the decoration layer 35 can be selected according to actual needs. For example, the decoration layer can include one or more layers of a TiN layer, a CrN layer, a TiCN layer, and a ZrN layer. The color of the decoration layer can be golden yellow, silver, silver black, or gunmetal color.

[0058] Optionally, the thickness of the decoration layer 35 is 0.5 μm-0.8 μm. For example, the thickness of the decoration layer 35 is 0.5 μm, 0.6 μm, 0.7 μm, or 0.8 μm.

[0059] In order to further improve the hardness of lightweight materials so that they can be used in wear-resistant parts, please refer to Figure 5 In another embodiment, the lightweight material 400 includes a magnesium-based metal substrate 41, a modified magnesium oxide ceramic layer 42, an aluminum-based primer layer 43, a transition layer 44, and a hardening layer 45, wherein the modified magnesium oxide ceramic layer 42 is located on the magnesium-based metal substrate 41, the aluminum-based primer layer 43 is located on the modified magnesium oxide ceramic layer 42, the transition layer 44 is located on the aluminum-based primer layer 43, the hardening layer 45 is located on the transition layer 44, and the density of the aluminum-based primer layer 43 is greater than that of the modified magnesium oxide ceramic layer 42. The magnesium-based metal substrate 41, the modified magnesium oxide ceramic layer 42, and the aluminum-based primer layer 43 constitute a lightweight substrate, the hardness of the transition layer 44 is greater than that of the lightweight substrate, and the hardness of the hardening layer 45 is greater than that of the transition layer 44.

[0060] In the above embodiment, a transition layer 44 is provided on the aluminum-based base layer 43, and a hardened layer 45 is provided on the transition layer 44. The hardness of the hardened layer is relatively large, so that the lightweight material can be applied to wear-resistant parts. At the same time, since the hardness of the hardened layer is quite different from the hardness of the lightweight substrate composed of the magnesium-based metal matrix 41, the modified magnesium oxide ceramic layer 42 and the aluminum-based base layer 43, if a transition layer with moderate hardness is not provided, the problem of the hardened layer falling off will occur when the lightweight material is subjected to external force. The provision of the transition layer can play a better buffering role when external force acts, and the hardened layer is not easy to fall off.

[0061] It can be understood that the lightweight substrate is composed of a magnesium-based metal substrate 41, a modified magnesium oxide ceramic layer 42 and an aluminum-based primer layer 43, and its hardness is the hardness of the entirety of the three. Optionally, the hardness of the lightweight substrate is 500HV to 700HV. For example, the hardness of the lightweight substrate is 500HV, 550HV, 600HV, 650HV, or 700HV.

[0062] The hardness of the transition layer 44 is between the hardness of the lightweight substrate and the hardness of the hardened layer 45. Optionally, the hardness of the transition layer 44 is 1500HV to 2000HV. For example, the hardness of the transition layer 44 is 1500HV, 1600HV, 1700HV, 1800HV, 1900HV, 2000HV. Optionally, the thickness of the transition layer 44 is 0.6μm to 1.0μm. For example, the thickness of the transition layer 44 is 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm.

[0063] Optionally, the transition layer 44 includes one or more layers of a CrN layer, a TiN layer, a CrAlN layer, a TiAlN layer, a MoAlN layer, and an AlTiN layer. Preferably, the transition layer 44 includes an Al element. In this case, the transition layer 44 has a better bonding force with the aluminum-based primer layer 43.

[0064] The hardness of the hardened layer 45 is relatively large, which can give the lightweight material better wear resistance. Optionally, the hardness of the hardened layer 45 is 2300HV to 3000HV. For example, the hardness of the hardened layer 45 is 2300HV, 2400HV, 2500HV, 2600HV, 2700HV, 2800HV, 2900HV, or 3000HV.

[0065] Optionally, the hardened layer includes one or more layers of a TiCN layer, a TiSiCN layer, a CrCN layer, a CrSiCN layer, a CrAlSiN layer, a CrMoSiN layer, a TiSiN layer, a TiMoN layer, a TiMoSiN layer and a TiMoCN layer.

[0066] Optionally, the thickness of the hardened layer 45 is 1.2 μm to 1.5 μm. For example, the thickness of the hardened layer 45 is 1.2 μm, 1.3 μm, 1.4 μm, or 1.5 μm.

[0067] The second aspect of the present application provides a method for preparing a lightweight material. In one embodiment, see Figure 6 , the preparation method of the lightweight material comprises the following steps:

[0068] S10. Forming a modified magnesium oxide ceramic layer on a magnesium-based metal substrate by micro-arc oxidation.

[0069] It can be understood that forming a modified magnesium oxide ceramic layer on a magnesium-based metal substrate by micro-arc oxidation includes the following steps:

[0070] The magnesium-based metal substrate is placed in an electrolyte, the magnesium-based metal substrate is used as an anode, and the stainless steel is used as a cathode. The power is turned on to electrolyze the electrolyte to form a modified magnesium oxide ceramic layer on the magnesium-based metal substrate.

[0071] Optionally, the process parameters of micro-arc oxidation include: an anodic oxidation voltage of 500 V to 700 V. The electrolyte of micro-arc oxidation includes an alkaline substance and a magnesium-containing compound, wherein the magnesium-containing compound includes one or more of magnesium chloride and magnesium sulfate. Optionally, the electrolyte also includes one or more of a silicon-containing compound and a phosphorus-containing compound.

[0072] The time of micro-arc oxidation is controlled to form a modified magnesium oxide ceramic layer with a thickness of 10 μm to 20 μm. At this time, the density of the modified magnesium oxide ceramic layer is 80% to 85%.

[0073] After the modified magnesium oxide ceramic layer is formed, the method further includes the steps of cleaning and drying the intermediate product.

[0074] S20, depositing an aluminum-based primer layer on the modified magnesium oxide ceramic layer by physical vapor deposition, wherein the density of the aluminum-based primer layer is greater than that of the modified magnesium oxide ceramic layer.

[0075] Optionally, the physical vapor deposition is magnetron sputtering. The magnesium-based metal substrate formed with the modified magnesium oxide ceramic layer can be placed in a magnetron sputtering furnace, and before the aluminum-based primer layer is sputtered and deposited, glow cleaning can be performed in the magnetron sputtering furnace, and the glow cleaning time can be 10 minutes to 20 minutes.

[0076] Optionally, the parameters of magnetron sputtering for depositing the aluminum-based bottom layer include: the power source is a DC power source, the nitrogen flow rate is 50 sccm to 100 sccm, the temperature is 80° C. to 100° C., and the target material is an aluminum-based target material, and a suitable target material can be selected according to the layer structure of the aluminum-based bottom layer described above.

[0077] The deposition time is controlled to form an aluminum-based primer layer with a thickness of 0.2 μm to 0.5 μm. At this time, the density of the aluminum-based primer layer is 92% to 95%.

[0078] The overall hardness of the magnesium-based metal substrate, the modified magnesium oxide ceramic layer and the aluminum-based primer layer is 500HV~700HV.

[0079] Compared with directly forming a single corrosion-resistant coating on a magnesium-based metal substrate by electroplating and chemical plating, the above method can avoid the damage to the environment caused by the waste liquid generated by electroplating and chemical plating, and the treatment cost is relatively low. Compared with directly forming a single corrosion-resistant coating on a magnesium-based metal substrate by anodizing and MAO, the lightweight material prepared by the above method has a more significant improvement in corrosion resistance. Compared with directly forming a single corrosion-resistant coating on a magnesium-based metal substrate by physical vapor deposition, the lightweight material prepared by the above method has better bonding strength among the layers.

[0080] See also Figure 7 In another embodiment, the method for preparing the lightweight material further comprises the following steps in addition to the above S10 and S20:

[0081] S30, depositing a dense reinforcement layer on the aluminum-based primer layer by physical vapor deposition, and controlling the power supply to be a pulse power supply so that the density of the dense reinforcement layer is greater than that of the aluminum-based primer layer.

[0082] The power source for depositing the dense reinforcement layer is a pulse power source. Compared with a DC power source, a pulse power source can provide a 5% to 10% duty cycle time to obtain a higher density coating. Optionally, the power source for depositing the dense reinforcement layer is a HiPiMS power source. It has higher energy and higher ionization rate, and can excite more ions in a short time, which is conducive to the formation of a dense reinforcement layer with higher density.

[0083] Optionally, the physical vapor deposition is magnetron sputtering.

[0084] Optionally, magnetron sputtering parameters for depositing the dense strengthening layer include: nitrogen flow rate of 80 sccm-130 sccm, temperature of 80° C.-100° C. A suitable target material can be selected according to the layer structure of the dense strengthening layer described above.

[0085] The deposition time is controlled to form a dense reinforcement layer with a thickness of 0.8 μm to 1.2 μm. At this time, the density of the dense reinforcement layer is 97% to 99%.

[0086] The above method forms a modified magnesium oxide ceramic layer on a magnesium-based metal substrate through micro-arc oxidation, and then forms an aluminum-based base layer and a dense reinforcement layer with gradually increasing density on the modified magnesium oxide ceramic layer through physical vapor deposition, which can significantly improve the problem of poor corrosion resistance of magnesium-based metals.

[0087] See also Figure 8 In another embodiment, the method for preparing the lightweight material further comprises the following steps in addition to the above S10, S20, and S30:

[0088] S40, forming a decorative layer on the dense reinforcement layer.

[0089] Optionally, the decorative layer is formed on the dense reinforcement layer by physical vapor deposition. Optionally, the physical vapor deposition is magnetron sputtering. The thickness of the formed decorative layer is 0.5 μm to 0.8 μm.

[0090] See also Fig. 9 In another embodiment, the method for preparing the lightweight material, in addition to the above S10 and S20, further comprises the following steps:

[0091] S50, depositing a transition layer on the aluminum-based primer layer.

[0092] The magnesium-based metal matrix, the modified magnesium oxide ceramic layer and the aluminum-based primer layer constitute a lightweight substrate, and the hardness of the transition layer is greater than the hardness of the lightweight substrate. Optionally, the hardness of the hardened layer is 1500HV~2000HV.

[0093] Optionally, a transition layer is deposited on the aluminum-based primer layer by physical vapor deposition. Optionally, the physical vapor deposition is magnetron sputtering. A suitable target material can be selected according to the layer structure of the transition layer above. The thickness of the formed transition layer is 0.6 μm to 1.0 μm.

[0094] S60, depositing a hardening layer on the transition layer.

[0095] The hardness of the hardened layer is greater than that of the transition layer. Optionally, the hardness of the hardened layer is 2300HV~3000HV.

[0096] Optionally, the hardening layer is deposited on the transition layer by physical vapor deposition. Optionally, the physical vapor deposition is magnetron sputtering. A suitable target material can be selected according to the layer structure of the hardening layer above. The thickness of the hardening layer formed is 1.2 μm to 1.5 μm.

[0097] The third aspect of the present application provides a middle frame. In one embodiment, the middle frame includes the above-mentioned lightweight material. Compared with a mobile phone middle frame formed by stainless steel or aluminum alloy, the weight of the mobile phone middle frame using the above-mentioned lightweight material can be reduced by 5g to 10g, which is a considerable weight reduction for mobile phones.

[0098] A fourth aspect of the present application provides an electronic device. In one embodiment, the electronic device includes a display module, a middle frame, a circuit board, and a housing. The middle frame includes the lightweight material as described above or the middle frame is as described above;

[0099] The display module, the middle frame and the housing are arranged to form a receiving space;

[0100] The circuit board is located in the accommodating space and is electrically connected to the display module.

[0101] The above-mentioned electronic devices have all the advantages of the above-mentioned lightweight materials, which will not be elaborated here.

[0102] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0103] Example 1

[0104] This embodiment provides a lightweight material and a preparation method thereof, and the specific steps are as follows:

[0105] S10, forming a modified magnesium oxide ceramic layer with a thickness of 15 μm and a density of 80% to 85% on a magnesium-based metal substrate by micro-arc oxidation, wherein the anodic oxidation voltage is controlled to be 600 V, and the electrolyte includes alkaline substances, magnesium chloride and magnesium sulfate. After alcohol ultrasonic cleaning, water washing and drying, a first intermediate product is obtained.

[0106] S20. Place the first intermediate product in a magnetron sputtering furnace, perform glow cleaning for 15 minutes, use direct current DC as power supply, use Al as target material, introduce 100 sccm of nitrogen, set the temperature to 100°C, and form an AlN layer with a thickness of 1.4μm and a density of 92%~95% on the modified magnesium oxide ceramic layer of the first intermediate product as an aluminum-based base layer to obtain a lightweight material. At this time, the lightweight hardness is 580HV.

[0107] Example 2

[0108] This embodiment provides a lightweight material and a preparation method thereof, the steps are as follows:

[0109] S10: Same as Example 1.

[0110] S20. Place the first intermediate product in a magnetron sputtering furnace, perform glow cleaning for 15 minutes, use direct current DC as power supply, use Al as target material, introduce 100 sccm of nitrogen, set the temperature to 100°C, and form an AlN layer with a thickness of 0.4 μm and a density of 92% to 95% on the modified magnesium oxide ceramic layer of the first intermediate product as an aluminum-based base layer to obtain a second intermediate product.

[0111] S30, using HiPiMS as a power source, introducing 80 sccm of nitrogen and 50 sccm of acetylene, setting the temperature to 80°C, and forming a TiCN layer with a thickness of 1 μm and a density of 97% to 99% on the AlN layer of the second intermediate product as a dense reinforcement layer to obtain a lightweight material.

[0112] The corrosion resistance of the lightweight materials of Example 1 and Example 2 was tested by using a neutral solution of NaCl with a mass fraction of 5% to perform a salt spray test for 24 hours. The test results are shown in Table 1.

[0113] Table 1

[0114]

[0115] It can be seen that the above-mentioned lightweight materials have good corrosion resistance, and in a chloride ion environment, the lightweight materials with a dense reinforcement layer can achieve better corrosion resistance.

[0116] Example 3

[0117] This embodiment provides a lightweight material and a preparation method thereof, the steps are as follows:

[0118] S10: Same as Example 1.

[0119] S20. Place the first intermediate product in a magnetron sputtering furnace, perform glow cleaning for 15 minutes, use direct current DC as power supply, use Al as target material, introduce 100 sccm of nitrogen, set the temperature to 100°C, and form an AlN layer with a thickness of 1.4 μm and a density of 92% to 95% on the modified magnesium oxide ceramic layer of the first intermediate product as an aluminum-based base layer to obtain a second intermediate product. The surface hardness of the second intermediate product is 580 HV.

[0120] S30, using direct current DC as a power source, forming a TiAlN layer with a thickness of 0.6 μm and a hardness of 1620 HV on the aluminum-based base layer as a transition layer, thereby obtaining a third intermediate product.

[0121] S40. Using direct current DC as a power source, a CrCN layer with a thickness of 1.2 μm and a hardness of 2460 HV is formed on the transition layer as a hardened layer to obtain a lightweight material.

[0122] Example 4

[0123] This embodiment provides a lightweight material and a preparation method thereof, the steps are as follows:

[0124] S10: Same as Example 1.

[0125] S20: Same as Example 3.

[0126] S30. Using direct current DC as power source, a CrCN layer with a thickness of 1.2 μm and a hardness of 2460 HV is formed on the aluminum-based base layer as a hardened layer to obtain a lightweight material.

[0127] The lightweight materials of Example 3 and Example 4 were taken, and the indentation method was used to characterize the bonding strength between the hardened layer and the substrate. First, the sample surface was cleaned. A Rockwell hardness tester was used, and a diamond indenter with a cone angle was selected to apply a force of 80 kgf. Then, the crack extension and morphology around the hardened layer were measured under a microscope. The grades were divided into 5 levels, namely Class Ⅰ to V. Class Ⅰ had the strongest bonding strength, and the hardened layer had no obvious cracks or peeling, and the hardened layer maintained integrity; Class Ⅱ had a strong bonding strength, and slight cracks appeared on the surface of the hardened layer, and no peeling occurred; Class Ⅲ had a moderate bonding strength, and obvious cracks appeared on the hardened layer, and peeling occurred locally; Class Ⅳ had a weak bonding strength, and large-area cracks or peeling appeared on the surface of the hardened layer, and the coating around the indentation fell off; Class Ⅴ had the weakest bonding strength, and the hardened layer was completely detached or peeled off in a large area. The test results are shown in Table 2.

[0128] Table 2

[0129]

[0130] It can be seen that if a transition layer with moderate hardness is not set, the hardened layer will fall off when the lightweight material is subjected to external force. If a transition layer is set, the middle layer with moderate hardness can play a better buffering role when external force acts, and the hardened layer is not easy to fall off.

[0131] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0132] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A lightweight material, characterized in that: include: Magnesium-based metal matrix; A modified magnesium oxide ceramic layer is located on the magnesium-based metal substrate; An aluminum-based primer layer is located on the modified magnesium oxide ceramic layer, and the density of the aluminum-based primer layer is greater than that of the modified magnesium oxide ceramic layer; The dense reinforcement layer is located on the aluminum-based primer layer, and the density of the dense reinforcement layer is greater than that of the aluminum-based primer layer.

2. The lightweight material according to claim 1, characterized in that: Includes at least one of the following features: (1) The density of the modified magnesium oxide ceramic layer is 80% to 85%; (2) The density of the aluminum-based primer layer is 92% to 95%; (3) The density of the dense reinforcement layer is 97% to 99%.

3. The lightweight material according to claim 1, characterized in that: The dense reinforcement layer is a single layer or includes multiple stacked reinforcement sub-layers.

4. The lightweight material according to claim 3, characterized in that: In the multiple reinforcement sub-layers, the content of at least one element in each reinforcement sub-layer increases gradually along the stacking direction.

5. The lightweight material according to claim 3, characterized in that: Include one of the following characteristics: (1) The single-layer dense reinforcement layer is selected from AlN layer, CrN layer, CrAlN layer, TiAlN layer, TiSiAlN layer, TiCN layer, CrCN layer, CrSiN layer or TiSiN layer; (2) Multiple layers The reinforcing sublayers are each independently selected from an AlN layer, a CrN layer, a CrAlN layer, a TiAlN layer, a TiSiAlN layer, a TiCN layer, a CrCN layer, CrSiN or TiSiN.

6. The lightweight material according to claim 5, characterized in that: The dense reinforcement layer includes Al element.

7. The lightweight material according to any one of claims 1 to 6, characterized in that: The thickness of the dense reinforcement layer is 0.8 μm to 1.2 μm.

8. The lightweight material according to any one of claims 1 to 6, characterized in that: The lightweight material further comprises a decorative layer, wherein the decorative layer is located on the dense reinforcement layer.

9. The lightweight material according to any one of claims 1 to 6, characterized in that: Includes at least one of the following features: (1) The modified magnesium oxide ceramic layer comprises Mg(OH)2 and Al2O3; (2) The thickness of the modified magnesium oxide ceramic layer is 10 μm to 20 μm; (3) The aluminum-based primer layer includes one or more layers of an Al layer, an AlN layer, and an AlON layer; (4) The thickness of the aluminum-based primer layer is 0.2 μm to 0.5 μm.

10. A method for preparing a lightweight material, characterized in that: The steps include: forming a modified magnesium oxide ceramic layer on a magnesium-based metal substrate by micro-arc oxidation; Depositing an aluminum-based primer layer on the modified magnesium oxide ceramic layer by physical vapor deposition, wherein the aluminum-based primer layer has a higher density than the modified magnesium oxide ceramic layer; A dense reinforcement layer is deposited on the aluminum-based primer layer by physical vapor deposition, and the power supply is controlled to be a pulse power supply, so that the density of the dense reinforcement layer is greater than that of the aluminum-based primer layer.

11. The method for preparing a lightweight material according to claim 10, characterized in that: The following steps are also included: A decorative layer is formed on the dense reinforcement layer.

12. A middle frame, characterized in that: It comprises the lightweight material according to any one of claims 1 to 9.

13. An electronic device, characterized in that: It comprises a display module, a middle frame, a circuit board and a housing, wherein the middle frame comprises the lightweight material according to any one of claims 1 to 9 or according to claim 12; The display module, the middle frame and the housing are arranged to form a receiving space; The circuit board is located in the accommodating space and is electrically connected to the display module.